CHARACTER-BASED LEADERSHIP IN IMPROVING THE QUALITY OF HIGHER MANAGEMENT - Achmad Nur Komari (MAN Insan Cendekia Jambi, 2022)
The leader has the characteristics, habits, temperament, character and personality of his own unique and distinctive so that his behavior and style that distinguishes him from others. This style or style of life will definitely color his behavior and leadership type. Leadership is an aspirational force, a creative spirit, and a moral force, which is able to influence members to change attitudes, so that they are in line with the wishes and aspirations of the leader. Some types of leadership in general are autocratic, charismatic, laisser faire, democratic, to make quality improvements. But if every time and in every case you have to give orders or directions, it will cause difficulties, because every time you want to do a good job it must be with the leadership's orders, and if there is no order from the leadership the work is not done well, then continuous improvement of the quality of performance will be difficult to implement. A leader motivates followers through a leadership style based on Indonesian Local Wisdom, namely a character-based leadership style in realizing this, currently a leadership management style that integrates 18 character building values into the leadership style of PT management is achieved so that the vision and mission of the College is achieved character based, leadership model, quality improvement, higher education, motivation.